Synthesis and Properties of Supramolecular Crops Based on PNZST Antiferroelectric Film - Feng Zhou (Advances in Materials Science and Engineering)
With the rapid development of ecological agriculture and the continuous changes of the ecological environment, crops are facing tremendous challenges. At the same time, people’s demand for the number and variety of crops is gradually increasing, so the synthesis and performance improvement of crops is imminent. The emergence of supramolecular crops has brought about huge changes in the yield of crops. In this paper, for the purpose of reducing the cost of crops and enhancing the ability of crops to adapt to the environment, PNZST antiferroelectric film materials are used to study the synthesis of supramolecular crops. Among them, rice, corn, and soybeans are used as reference objects for synthetic crops. Experiments were carried out in four aspects: growth rate, growth cycle, and yield. The growth status of the three crops in the past four years was monitored and recorded and analyzed. The survival rate of traditional rice was 86.3%–89.5%, the growth cycle was 86–90 days, and the yield was 69–77 kg/ha; the survival rate of traditional corn was 85.6%–89%, the growth cycle was 105–114 days, and the yield was 38–43 kg/ha; the survival rate of traditional soybean was 85.6%–89%, the growth cycle was 85–90 days, and the output was 14–16 kg/ha. The survival rate of synthetic rice was 95.5%–96.9%, the growth cycle was 63–66 days, and the yield was 83–86 kg/ha; the survival rate of synthetic corn was 97.3%–98.7%, the growth cycle was 85–95 days, and the yield was 53–56 kg/ha; the survival rate of synthetic soybeans was 96.3%–98.3%, the growth cycle was 59–68 days, and the yield was 29–33 kg/ha.